Rheological characterization of gelling polymers for pharmaceutical dosage forms - Abdul Qader, Omar Abdul Jabbar; Doolaanea, Abd Almonem; Abdul Rahman, Mohammad Nasrin; Sukmasari, Susi; Ismail, Ahmad Faisal; khashman, Basim M. (2017)
Objective: This study aimed to characterize several gelling polymers as candidates to be developed as pharmaceutical vehicles. Significance: This study opens up more options for pharmaceutical semi-solid vehicle formulator to choose regarding the range of gelling polymers, as the vehicle for their pharmaceutical active ingredients. Methods: Five types of gelling polymers (acacia gum, methocel K100M, kelcogel LT100, lambda carrageenan, and locust bean gum) which consist of three different concentrations each, were prepared. The rheological profiles were measured using rheometers, and the data was analyzed to compare their apparent viscosities at various shear rates as well as rheological modelling. Results: At shear rates of 10 s-1, 50 s-1, and 100 s-1, 3% and 5% of kelcogel LT100 as well as 3% and 5% of methocel K100M possessed significantly the highest mean apparent viscosity (Pas). Acacia gum at concentration of 1%, 3% and 5% exhibited the lowest mean apparent viscosity (Pas) (p > 0.05). Each gel possessed different rheological modeling in different concentration, except for lambda carrageenan which possessed Ostwald De-Walele modelling in all concentrations. Among the gel with good regressions, kelcogel LT100 (1% and 5%) had the highest yield stress. Lambda carrageenan (5%) was found to be the most pseudoplastic based on its lowest flow behaviour index (n), and it also possessed the highest consistency factor (k) value. Conclusion: All the rheological profiles for each of the gels at three different concentrations were successfully characterized, analyzed and documented.